Caja Vecina, Keep Growing in an environment of technological changes - Oliva Becerra, Ismael; Jancso Acuña, Marta; Barriga Alarcón, Karla (Estudios de Administración, 2019)
Towards the end of 2016, CajaVecina, a subsidiary of BancoEstado of Chile - the country’s only state-owned commercial bank - celebrated its 10th anniversary. The subsidiary was born as a business model that sought to democratize financial services for all sectors of the country, and it was implemented in small businesses through an electronic POS device. More than 12 million clients and non-clients of BancoEstado carry out transactions online. Over time, CajaVecina became the largest and most successful bank correspondent service in the country, with a network of financial and non-financial services distributed throughout the country through the “neighborhood stores” (tiendas de barrio), with over 19,000 network points. Nevertheless, BancoEstado and CajaVecina were facing new challenges. The large number of clients and transactions were not easy to sustain and made it necessary to quickly implement a “digitalization strategy” proposed by the Executive Committee for the years 2017- 2020. CajaVecina’s General Manager, Marta Jancso, was aware that although she had the most extensive service network in the country (equivalent to more than 8 times the number of banking branches existing in Chile), a re-thinking of the organization’s strategy, on the point of starting the new budget year, was a real necessity. She looked at the transactional map of BancoEstado’s clients and the Bank’s digitalization strategy for the same period and wondered if CajaVecina should continue to expand its network and its services using the current format, or adjust its strategy, offering added value, services and technology, or simply sit back and wait while financial transactions over cell phones and the Internet ended up terminating the decade-long successful run of CajaVecina.